Guns and college homicide: the case to prohibit firearms on campus - Boss, Stephen K. (McFarland & Company, Inc., Publishers, 2019)
"At a time when mass shootings in schools and other public spaces have become commonplace, it might seem surprising that American college campuses are not magnets for murderers but sanctuaries from them. Due to remarkably effective gun-safe policies, deaths by firearms on college campuses are 1,000 times less frequent than in the U.S. public at large"--